Characteristics of Patients with VP Shunt Malfunction in Dr. Mohammad Hoesin General Hospital between May 2018 and July 2019 - Argo Ismoyo; Anugerah Onie (Surgery Department, Faculty of Medicine Universitas Sriwijaya, 2021)
Introduction: Hydrocephalus may occur when the production of cerebrospinal fluid (CSF) is excessive or, the most common cause when, the absorption of CSF is decreased. The VP Shunt is most commonly performed worldwide as the primary treatment for hydrocephalus. The complications of VP Shunt are shunt infection, mechanical malfunction and over or under-drainage. This study aims to see the characteristics of patients affected by post VP shunt infection who are treated at dr. Mohammad Hoesin Palembang Methods: This research was a cross-sectional descriptive study. Using secondary data from the medical records of Mohammad Hoesin Hospital, Palembang. Performed in the from May 2018 to July 2019. Samples were all patients diagnosed with malfunction and infection with VP Shunt. Results: There were 23 subjects participated who met study critera. VP shunt infections were mostly male (82.6%). The largest age distribution is less than 1 year old (39.1%). The most incidence occured at the age of 1-6 months (60.9%). The most common type of surgery was emergency surgery (60.8%). The most common malfunctions were caused by shunt malfunctions (69.6%). Conclusion: Male patients, patients age <1 year old with onset of 1-6 months, and shunt malfunctons were the most common characteristic of patients diagnosed with malfunction and infection with VP Shunt.